2018
DOI: 10.1111/acer.13889
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Use and Risk of Harmful Alcohol Consumption in the U.S. Population

Abstract: E-cigarette users, particularly those who engage in nondaily and dual use, show elevated rates of harmful alcohol use. Heavy drinking may constitute a source of health risk among e-cigarette users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…In another study looking at e-cigarette use in adult never smokers (never smokers included current smokers who were not smokers a year ago), black people and Hispanics had decreased odds of current and regular e-cigarette use, while unmarried participants had increased odds of current and regular e-cigarette use [ 73 ]. E-cigarette use has also been shown to be associated with alcohol use and alcohol use disorder in nonsmokers of cigarettes [ 74 ]. Associations with asthma [ 18 ] and depression [ 13 ] have also been reported for sole e-cigarette use.…”
Section: Discussionmentioning
confidence: 99%
“…In another study looking at e-cigarette use in adult never smokers (never smokers included current smokers who were not smokers a year ago), black people and Hispanics had decreased odds of current and regular e-cigarette use, while unmarried participants had increased odds of current and regular e-cigarette use [ 73 ]. E-cigarette use has also been shown to be associated with alcohol use and alcohol use disorder in nonsmokers of cigarettes [ 74 ]. Associations with asthma [ 18 ] and depression [ 13 ] have also been reported for sole e-cigarette use.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of epidemiological datasets find that tobacco cigarette users are significantly more likely to meet criteria for alcohol use disorders (AUD) and to meet hazardous drinking criteria (McKee et al, 2007). Similar studies found that people who use other nicotine delivery devices (e.g., electronic cigarettes; Roberts et al, 2018a) also showed elevated rates of AUD and hazardous alcohol use relative to the general population. Eventlevel data suggest that smokers consume more alcohol during occasions where they also smoke (Witkiewitz et al, 2012), and people being successfully treated for alcohol use also show a corresponding reduction in smoking (Roberts et al, 2018b).…”
Section: Introductionmentioning
confidence: 89%
“…E-cigarettes are marketed and used as alternatives to cigarettes [ 14 , 15 ]. E-cigarette use is positively correlated with cigarette smoking and has been associated with increased levels of alcohol, marijuana, and other substance use [ 5 , 7 , 16 , 17 , 18 ]. In addition, although used mainly for nicotine consumption, e-cigarettes are also used to vape marijuana [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%